A facile synthesis of Ni0.85Se@Cu2−xSe nanorods as high-performance supercapacitor electrode materials. Issue 38 (10th September 2021) - Liu, Shuling; Wang, Rui; Wang, Qiuting; Tian, Qianhong; Cui, Xian
Abstract : The as-prepared Ni0.85 Se@Cu2− x Se nanorod-like electrode exhibits superior electrochemical performance for supercapacitors. Abstract : Transition-metal selenides are regarded as promising electrode materials due to their superior electrochemical performances for supercapacitors. In this study, a nanorod-like hybrid of Ni0.85 Se@Cu2− x Se on a Ni-foam substrate is successfully synthesized via a facile one-step route. The Ni0.85 Se@Cu2− x Se nanorods are found to be deposited uniformly on the Ni-form substrates. When used as a battery-type electrode in a supercapacitor, the as-deposited Ni0.85 Se@Cu2− x Se electrode exhibits a high specific capacity of 1831 F g −1 at 1 A g −1 and 78.4% of capacitance retention after 8000 cycles at 10 A g −1 . Moreover, the assembled Ni0.85 Se@Cu2− x Se//AC asymmetric supercapacitor (ASC) exhibits an energy density of 63.2 W h kg −1 at a power density of 800.1 W kg −1, as well as good cycling stability (92.1% capacitance retention after 5000 cycles).